Association between Maximal Aerobic Capacity and Psychosocial Factors in Adults With Moderate-to-Severe Asthma. (August 2013) - Mendes, Felipe A.R.; Lunardi, Adriana C.; Silva, Ronaldo A.; Cukier, Alberto; Stelmach, Rafael; Martins, Milton A.; Carvalho, Celso R.F.
Abstract : Background. The symptoms of asthma impair health-related quality of life (HRQoL), increase anxiety and depression and may keep subjects from engaging in physical exercise. Physical inactivity has been related to poor asthma outcomes; however, the association between physical fitness and psychosocial disorders remains poorly understood. Objective. To verify the association between aerobic capacity, HRQoL, and psychological distress in adults with moderate or severe persistent asthma who were clinically stable. Methods. Eighty-eight participants (68 females) with either moderate or severe persistent asthma (age range, 20–60 years) who were under medical treatment for at least 6 months and considered clinically stable were studied. Participants were evaluated on two non-consecutive days. On the first day, the HRQoL, depression and anxiety levels and pulmonary function were assessed. On the second day, subjects underwent cardiopulmonary exercise testing. Results. Using the agglomerative cluster approach, two clusters were identified: 21 participants (24%) were grouped in Cluster 1, and 67 (76%) were grouped in Cluster 2. Asthmatic subjects from Cluster 1 exhibited increased aerobic capacity, better HRQoL and lower depression levels than did subjects in Cluster 2 ( p < .05). No difference was observed between the clusters with respect to gender, age, body mass index (BMI) or pulmonary function ( p > .05). The discriminant function model exhibits good accuracy ( R 2 = 0.79) and predicted 93% of the case allocations. Conclusion. Our results suggest an association between reduced exercise capacity, low HRQoL and increases in depressive symptoms in clinically stable asthmatic subjects. These results suggest the need to assess physical fitness and psychosocial distress during asthma treatment and the importance of a multidisciplinary approach.